(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Research of different studies related to collaboration municipality ─ university allows to establish a fact that it is very important for both partners and has distinctive forms. The core questions of this research are as follows: Is the regional university significant player in regional sustainable tourism development? What forms of collaboration among regional university and municipality are possible? The aim of this research is to examine the experience of regional university in sustainable tourism development in regional area. This research is performed on the illustration of collaboration among regional university (Rezeknes Augstskola ) and Dagda county, which is one of the 19-th rural county in Latgale region. A new approach to the collaboration municipality ─ regional university is offered taking into account the possibilities of regional university in improvement of human resources capacity, in improvement of municipality administrative capacity, and in development of sustainable tourism products. The offered approach was set up by taking into account the interests of all stakeholders in this area.